PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA PADA KASUS KEGAWATDARURATAN DI LINGKUNGAN SEKOLAH DENGAN METODE DRILL BAGI KADAR KESEHATAN SEKOLAH MTSN 1 BENGKULU UTARA - Desi Susilawati; Tuti Anggriani Utama; Feni Eka Dianti (Jurnal Pengabdian Kepada Masyarakat, 2022)
The partner problem at MTSN I Bengkulu Utara is that students still get accidents in the school environment. This is a very serious concern because school facilities and the limitations of the school in emergency first aid are still lacking. The purpose of the activity is to increase the ability of MTSN I North Bengkulu cadres in emergency first aid in the school environment. The methods used are: drill method through lectures, demonstrations, discussions, questions and answers, and companion partners. The results achieved are (1) partners have knowledge in providing emergency first aid and partners have attitudes and are able to take action to provide emergency first aid. The activity was carried out on June 29, 2022 at MTSN I North Bengkulu. Before the student cadres get the material, the cadres do pre and post tests as an evaluation of activities. Participants were followed by 30 people who were selected from the school as emergency first aid cadres (KAPEPEGA). The results obtained are participants are very enthusiastic about participating and getting pre test results, most of the respondents in the category of sufficient knowledge are 20 people (66.7%), respondents with less knowledge category are 6 people (20%) and the rest are respondents with good knowledge category as many as 4 people (13,3%). The results of the post test showed that most of the respondents were in the good knowledge category, namely 21 people (70%) and the rest of the respondents with sufficient knowledge category were 9 people (30%). The attitude of the participants with the pre test results of all respondents included in the category of positive attitudes as many as 30 people (100%) and the post test results revealed that all respondents were included in the category of positive attitudes, namely 30 people (100%). The skills of the participants with the pre test results of all respondents included in the poor skill category as many as 29 people (96.7%) and the post test results revealed that all respondents were included in the good skills category of 30 people (100%). The difference between pre and post on knowledge and action has a value of sig 0.05, it can be stated that there is a significant difference between the results of the pre test and the results of the post test on knowledge and action, meaning that there is a significant difference in the knowledge and actions of school health cadres in MTSN 1 Bengkulu Utara after the provision of drill method health education. On the attitude obtained a sig value 0.05, it can be stated that there is no significant difference between the pre test results and the post test results on attitudes, meaning that there is no significant difference in the attitudes of school health cadres at MTSN 1 Bengkulu Utara after providing health education with the drill method. The conclusion of this activity is that the results of community service show a positive impact for MTSN I North Bengkulu cadres in emergency first aid. Suggestions for MTSN I can apply and make excellence for schools about emergency first aid in the school environment. Keywords: First Aid, emergency